World media ethics cases and commentary - Fortner, Robert S.; Fackler, Mark (Hoboken, New Jersey John Wiley & Sons Inc., 2018)
"Emphasizing the intertwined concepts of freedom of the press and social responsibility, this is the first book to cover media ethics from a truly global perspective. Case studies on hot topics and issues of enduring importance in media studies are introduced and thoroughly analyzed, with particular focus on ones involving social media and public protest Written by two global media ethics experts with extensive teaching experience, this work covers the whole spectrum of media, from news, film, and television, to advertising, PR, and digital media End-of-chapter exercises, discussion questions, and commentary boxes from a global group of scholars reinforce student learning, engage readers, and offer diverse perspectives"--Provided by publisher.
"The first book to cover media ethics from a truly global perspective, emphasizing the intertwined concepts of freedom of the press and social responsibility"--Provided by publisher.
Introduction : Contexts for ethical decision-making -- Philosophical perspectives on ethical decision-making: the individualist tradition -- Philosophical perspectives on ethical decision-making: the collectivist traditions -- Ethics and political economy -- Boundaries on civil discourse -- Advertising, public relations and materialism -- Global entertainment -- Media and the political process -- The rule of law -- Treasuring persons, protecting institutions: the protection of minority voices -- Religion and social responsibility -- War, violence, and Media -- Truth, conflict, chronic problems and media attention -- Conclusion -- Glossary.
Includes bibliographical references and index.
Keywords: Mass media -- Moral and ethical aspects